Answer:
2
Step-by-step explanation:
2k+3=7
2k=4
k=2
Average rate of change = change in y ÷ change in x
We already know the change in x because we are measuring the x values from -3 to 0.
change in x = 0-(-3) = 3
To find the change in y find the difference between the corresponding y-values when x=0 and when x=-3.
change in y = 0.5-2 = -1.5
average rate of change = -1.5/3 = -0.5
answer: -0.5
total number of outcomes =2^5=32 hope this helps.
Answer:
106°
Step-by-step explanation:
Supplementary angles total 180°, so the one supplementary to 74° is ...
180° -74° = 106°
Answer:
Step-by-step explanation:
This is your answer